1970
DOI: 10.1037/h0028884
|View full text |Cite
|
Sign up to set email alerts
|

Effects of facilitative interpersonal functioning in a conditioning paradigm.

Abstract: Using a fixed-choice procedure 28 subjects were conditioned to emit personal reference statements by two experimenters functioning high on the dimensions of empathy, positive regard, and genuineness and two low-functioning experimenters. Comparison of learning slopes of conditioned subjects with a control group supported the efficacy of the facilitative dimensions for the conditioning paradigm.Research in psychotherapy has underscored the efficacy of therapist empathy, positive regard, and genuineness in deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1971
1971
1982
1982

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 6 publications
1
25
0
Order By: Relevance
“…Brady et al state that &dquo;the only known deviation from Vitalo's (1970) study is that the number of subjects was increased from 28 to 32.&dquo;5 A critical difference in the results of the two studies was that Vitalo reported an F of 13.10 (p < .005) for an experimenters x conditions interaction, while Brady et al obtained an F of only 1.54 (n.s.). The problem becomes clear when the SS for error is examined, for it is 2.40 in the first study and 19.88 in the second.…”
Section: Experimental Precisionmentioning
confidence: 96%
See 2 more Smart Citations
“…Brady et al state that &dquo;the only known deviation from Vitalo's (1970) study is that the number of subjects was increased from 28 to 32.&dquo;5 A critical difference in the results of the two studies was that Vitalo reported an F of 13.10 (p < .005) for an experimenters x conditions interaction, while Brady et al obtained an F of only 1.54 (n.s.). The problem becomes clear when the SS for error is examined, for it is 2.40 in the first study and 19.88 in the second.…”
Section: Experimental Precisionmentioning
confidence: 96%
“…Since effect sizes are typically of small absolute magnitude, the undesirable feature of accounting for more than 100% variance would not likely be discovered by researchers. Table 1 (taken from Vitalo, 1970) allow comparisons in the one-way ANOVA as well as this two-way case. Here, the proportion of variance accounted for by sources is smaller than proportions in the Byrne and Rhamey study.…”
Section: Comparisons Among Effect Size Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…To fulfill this responsibility we must live with courage and vigor, extending ourselves across the physical, emotional, and intellectual spheres of living. We must "relate with those qualities that research has defined as critical to effectiveness including the responsive dimensions of empathy, respect, and concreteness and the initiative dimensions of genuineness, confrontation, and immediacy Anderson, Douds, & Carkhuff, 1967;Aspy, 1969;Aspy & Haddock, 1967;Berenson, Mitchell, & Moravic, 1968;Bergin, 1966;Carkhuff, 1969;Carkhuff & Griffin, 1972;Carkhuff, Pierce, & Berenson, 1967;Christensen, 1960;Dickenson & Truax, 1966;Dixon & Morse, 1961;Hefele, 1971;Hountras & Anderson, 1969;Johnson, 1971;Mickelson & Stevic, 1971;Mullen & Abeles, 1971;Piaget, Berenson, & Carkhuff, 1967;Rogers, Gendlin, & Truax, 1967;Shapiro & Voog, 1969;Truax, 1963;Truax & Carkhuff, 1964, 1967Truax, Carkhuff, & Kodman, 1965;Truax & Tatum, 1966;Truax, Wargo, & Wilber, 1966;Van de Veen, 1967;Vitalo, 1970). Further, we must relate with those qualities within the context of our own lives as well as within the context of helping.…”
Section: People Make the Differencementioning
confidence: 97%
“…Effective people require systematic programs in order to deliver to those whom they serve (Carkhuff, 1971;Mickelson & Stevic, 1971;Vitalo, 1970). Programs cannot stand alone and effective people cannot make efficient impact through vague and unsystematic means.…”
Section: Systematic Programs the Way To Effective Deliverymentioning
confidence: 98%